Cultivating Effective Educators: Experiential Learning in Korean Language Teacher Education - Chung, Ji Hoon; Choi, Yeseul; Kim, Nayoung; You, Minji; Yoo, Theodore Jun (International Journal of Korean Humanities and Social Sciences, 2025)
The global rise in Korean language education, driven by the growing influence of the Korean Wave (Hallyu), has sparked a need for innovative teaching methods to effectively address the needs of an increasingly diverse community of learners. This study examines the effectiveness of experiential learning programs in Korean language teacher education, focusing on their role in developing pedagogical competencies, shaping professional identities, and preparing educators for multicultural classrooms. By integrating hands-on, immersive activities such as classroom simulations, practicum placements, and community engagement projects, experiential learning enables future educators to bridge theory and practice, fostering deeper language proficiency and cultural understanding. Grounded in Situated Learning Theory and Possible Selves Theory, the research demonstrates how real-world teaching experiences not only enhance instructional skills but also broaden career aspirations and cross-cultural competencies among teacher candidates. The study further examines institutional responses to the growing demand for Korean language instruction, including curriculum innovations at leading universities and the expansion of international language programs. As Korean language education undergoes a paradigm shift driven by global cultural engagement and domestic demographic changes, this study contributes to the evolving discourse on effective teaching methodologies, underscoring the importance of adaptability, cross-cultural competency, and experiential learning in shaping the future of Korean language educators.